El derecho internacional privado y el derecho comunitario - Abelardo Posso Serrano (Universidad Hemisferios, 2010)
Private international law is justified at a time when the legal systems of nation states seeking a way to extend their areas and competencies. This desire led to the conflict between national laws, which grew smaller as did the novel concept of